Pioneers, Imitators, and Generics–A Simulation Model of Schumpeterian Competition - Grabowski, Henry G.; Vernon, John M. (Quarterly Journal of Economics, 1987)
A computer simulation model in the tradition of evolutionary models of technical change is developed in this paper. It focuses on R&D competition in new product introductions and is based on data for the U. S. pharmaceutical industry during the 1970s. The sensitivity of innovation levels to the rate of generic competition, regulatory review time, and patent life is examined in the computer simulation experiments. These factors are found to have significant long-run effects on industry structure and innovation levels.